History of exercise physiology (Human Kinetics, 2014)
From studying great thinkers of antiquity and work done by pioneers at research institutions, to exploring the inner workings of all the body's systems, this book helps researchers gain a precise understanding of what happens when human bodies move and who influenced and furthered that understanding.